2012
DOI: 10.1111/j.1559-1816.2012.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits That Predict Academic Citizenship Behavior

Abstract: The association between personality and organizational citizenship behaviors is rarely examined in student populations. The present research tested the hypothesis that conscientiousness, agreeableness, and neuroticism predict unique variance in academic citizenship attitudes. In the first study, 270 college students completed an online questionnaire assessing their personality and academic citizenship attitudes. The results confirmed the hypothesis. In Study 2, we also tested the hypothesis that academic citiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
0
13
0
3
Order By: Relevance
“…CP has been frequently assessed and studied in organizational research (i.e., [42,43]). However, the assessment of this variable in the educational domain is very rare (see, for instance, [44]). In addition, the relationship between dishonest behaviors (counterproductive work behaviors) and contextual performance has largely been examined in organizational contexts (see [43,45]), showing a negative association between the constructs (see [46,47]).…”
Section: Academic Dishonesty (Ad) and Contextual Performance (Cp)mentioning
confidence: 99%
“…CP has been frequently assessed and studied in organizational research (i.e., [42,43]). However, the assessment of this variable in the educational domain is very rare (see, for instance, [44]). In addition, the relationship between dishonest behaviors (counterproductive work behaviors) and contextual performance has largely been examined in organizational contexts (see [43,45]), showing a negative association between the constructs (see [46,47]).…”
Section: Academic Dishonesty (Ad) and Contextual Performance (Cp)mentioning
confidence: 99%
“…Gore and colleagues found that conscientiousness measurements within the 5-factor inventory was associated with being a good academic citizen, which could relate to being a good team member in a cooperative environment. 28 Using the 5-factor inventory and a learning styles inventory, Komarraju and colleagues found that personality and learning styles explained a small fraction of the variance in GPA, American Journal of Pharmaceutical Education 2015; 79 (2) Article 20.…”
Section: Discussionmentioning
confidence: 99%
“…ne uwarunkowaniom i determinantom zachowań obywatelskich wskazują między innymi, że zachowania te są silnie zależne od dyspozycji jednostki (tzn. osobowości, emocji) (Greguras, Diefendorff, 2010: 551;Gore, Kiefner, Combs, 2012: 2438, postaw pracowników (Cohen, 2006), postrzegania organizacji (Fassina, Jones, Uggerslev, 2008) oraz oceny jej funkcjonowania (Britt i wsp., 2012), a także stylu kierowania przełożonych (Organ, Podsakoff, MacKenzie, 2006: 95-109). Na polskim gruncie naukowym temat ten jak dotąd nie był szeroko eksplorowany przez badaczy.…”
Section: Wprowadzenieunclassified
“…Wszyscy respondenci twierdzili, że wpływ na skłonność do podejmowania lub niepodejmowania zachowań OCB mają: osobowość, wyznawane wartości i postawy, co jest zbieżne z badaniami innych autorów (np. Cohen, 2006;Greguras, Diefendorff, 2010;Gore, Kiefner, Combs, 2012). Zdaniem wszystkich uczestników badania zachowania OCB mogą poprawiać wizerunek pracownika, zwiększać szansę na awans lub dodatkową premię, dlatego nie są podejmowane zupełnie bezinteresownie.…”
Section: Podsumowanieunclassified